1968
DOI: 10.1002/ar.1091610409
|View full text |Cite
|
Sign up to set email alerts
|

Sperm maturation in the male reproductive tract: Development of motility

Abstract: Rabbit spermatozoa were removed from various levels of the male reproductive tract. They were examined in Hanks' solution at room temperature with a phase contrast microscope and their motility characteristics were recorded cinematographically. Spermatozoa from the seminiferous tubules and ductuli efferentes show weak, vibratory movements with no forward progress. Little change in motility occurs until the sperm reach the flexure of the caput epididymidis where some are capable of moving more vigorously in a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
1
1

Year Published

1972
1972
1996
1996

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(32 citation statements)
references
References 14 publications
3
27
1
1
Order By: Relevance
“…Stimulation was not observed before 10 min of incubation ; peak activity occurred around 25 min and decreased rapidly after 30 min of incubation ( fig. 3) Earlier studies in many species have reported similar observations (for review see Gaddum, 1968). The potential for forward motility occurs as the spermatozoa pass through the epididymis, and the capacity for forward movement is acquired in different regions of that organ, depending on the species studied.…”
Section: Introductionmentioning
confidence: 68%
“…Stimulation was not observed before 10 min of incubation ; peak activity occurred around 25 min and decreased rapidly after 30 min of incubation ( fig. 3) Earlier studies in many species have reported similar observations (for review see Gaddum, 1968). The potential for forward motility occurs as the spermatozoa pass through the epididymis, and the capacity for forward movement is acquired in different regions of that organ, depending on the species studied.…”
Section: Introductionmentioning
confidence: 68%
“…The pattern of sperm motility in various regions of the epididymis has been studied in several species (Tournade, 1913;Blandau & Rumery, 1964;Gaddum, 1968;Fray, Hoffer & Fawcett, 1972;Burgos & Tovar, 1974), but there have been relatively few studies concerned with the measurement of the motility of spermatozoa from distinct sites along the mammalian epididymis. This is probably due to the lack of adequate in¬ struments designed to quantify sperm motility and also of techniques available for obtaining samples of spermatozoa from distinct areas along the epididymis.…”
Section: Introductionmentioning
confidence: 99%
“…Although physiological changes (primarily motility) and subtle morphological changes occur during the epididymal maturation of spermatozoa from many eutherian species (BEDFORD, 1963(BEDFORD, , 1975BEDFORD and CALVIN, 1974;BEDFORD, CALVIN and COOPER, 1973;BLANDAU and RUMERY, 1964;CALVIN and BEDFORD, 1971;FAWCETT and HOLLENBERG, 1963;FAWCETT and PHILLIPS, 1969;FRAY, HOFFER and FAWCETT, 1972;GADDUM, 1968), such changes are not nearly as marked as they are in the metatherian forms. The marsupial species are unique in that they exhibit definite changes in morphology (associated with maturation) during their transit through the epididymis.…”
Section: Discussionmentioning
confidence: 99%